2023
DOI: 10.1108/cg-05-2022-0205
|View full text |Cite
|
Sign up to set email alerts
|

CEO characteristics and firm performance: evidence from a Southeast Asian country

Abstract: Purpose The purpose of this study was to investigate how chief executive officer (CEO) characteristics, including age, education, nationality and particularly gender, influence firm performance in a developing Southeast Asian Country (Indonesia). Design/methodology/approach The study uses balanced firm-level panel data for 203 nonfinancial companies listed on the Indonesia Stock Exchange from 2010 to 2020. Return on assets, return on equity and Tobin’s Q were used to measure firm performance. The data were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 138 publications
1
5
0
Order By: Relevance
“…CEO Gender: Espinosa-Mendez and Correa (2022) used a Chilean sample to observe superior financial performance in SMEs led by female CEOs. A similar result was obtained by Suherman et al (2023) for an Indonesian sample, with female CEOs providing objectivity in the assessment of management. A plethora of earlier studies concurred with Kotiranta et al (2007), Adams et al (2009), andNg (2017).…”
Section: Ceo Charateristics That Influence Firm Performance In Non-fa...supporting
confidence: 78%
See 1 more Smart Citation
“…CEO Gender: Espinosa-Mendez and Correa (2022) used a Chilean sample to observe superior financial performance in SMEs led by female CEOs. A similar result was obtained by Suherman et al (2023) for an Indonesian sample, with female CEOs providing objectivity in the assessment of management. A plethora of earlier studies concurred with Kotiranta et al (2007), Adams et al (2009), andNg (2017).…”
Section: Ceo Charateristics That Influence Firm Performance In Non-fa...supporting
confidence: 78%
“…Peterson et al (2001), Huang et al (2012) and Belot and Serve (2018) observed that older CEOs positively influenced financial reporting quality. Conversely, using a sample of Indonesian firms, Suherman et al (2023) observed that older CEOs were conservative and averse to the necessary risk taking needed to explore new products and markets. Consequently, their firms underperformed.…”
Section: Ceo Charateristics That Influence Firm Performance In Non-fa...mentioning
confidence: 97%
“…Furthermore, the discourse surrounding the relationship between women on boards and a firm's capital structure remains unresolved. toward risk aversion (Cardillo et al, 2021;Suherman et al, 2023b). Notably, Palvia et al (2015) highlighted that female chief executive officers (CEOs) take a more cautious approach to executing corporate strategies than their male counterparts owing to their lower risk preferences.…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia's corporate governance structure does not adhere to a one-tier system. In such a system, the board of directors and the board of commissioners are integrated into a single entity, in which board members bear the responsibility for making both operational and strategic decisions for the company (Darmadi, 2011;Khan et al, 2020;Suherman et al, 2021b;2023a, 2023b. In contrast, a two-tier system contains a distinct board of directors and a separate board of commissioners, with the latter being tasked with overseeing the performance of the former.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation